1996
DOI: 10.1016/s0896-6273(00)80103-8
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide: An Endogenous Modulator of the Nitric Oxide–Cyclic GMP Signaling System

Abstract: Carbon monoxide (CO) is an activator of soluble guanylyl cyclase and is implicated as a neuronal messenger. CO production, nitric oxide synthase (NOS) activity, and guanosine 3',5'-monophosphate (cGMP) levels were quantitated in cerebellar granule cell cultures. Metabolic labeling experiments enabled the direct measurement of neuronal CO production in vitro. CO production is significant, and peaked during early stages of culture. NOS activity and cGMP levels synchronously increased as cells matured. Whereas in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
161
4
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(172 citation statements)
references
References 48 publications
(9 reference statements)
6
161
4
1
Order By: Relevance
“…In rat brain slices, electrical field stimulation leads to Ca 2ϩ waves spreading from the astrocytic soma to the end feet (11). In the present study, we observed that glutamate causes Ca 2ϩ transients at 10 CO production has been measured in neurons (16), vascular smooth muscle cells (21,29), endothelial cells (21), and astrocytes (this study). In the cerebral vasculature, glutamate stimulates CO production in astrocytes (26) and endothelial cells (21).…”
Section: Discussionsupporting
confidence: 66%
“…In rat brain slices, electrical field stimulation leads to Ca 2ϩ waves spreading from the astrocytic soma to the end feet (11). In the present study, we observed that glutamate causes Ca 2ϩ transients at 10 CO production has been measured in neurons (16), vascular smooth muscle cells (21,29), endothelial cells (21), and astrocytes (this study). In the cerebral vasculature, glutamate stimulates CO production in astrocytes (26) and endothelial cells (21).…”
Section: Discussionsupporting
confidence: 66%
“…(i) In vitro, micromolar concentrations of CO have been shown to impair DNA binding and BMAL-heterodimer formation of heme-bound NPAS2 but not apo-NPAS2 (ref. 6), and in the brain, these concentrations of CO are generated by heme oxygenases 32 (detailed discussion of CO concentration in Supplementary Note 1). (ii) Mutation of heme-coordinating residues within NPAS2 also impairs heterodimer formation with BMAL1, thus decreasing both specific DNA binding to canonical E boxes and NPAS2-BMAL1 transactivation activity, probably via conformational changes within the PAS-A domain of NPAS2 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…HO-3 is a recently identified isoform and appeares to regulate heme-dependent genes (Magnusson et al, 2000). CO, like nitric oxide (NO), binds to the heme moeity of soluble guanylate cyclase (sGC) (Brune et al, 1990;Verma et al, 1993;Ingi et al, 1996a;Snyder et al, 1998) and in cultured olfactory neurons HO inhibitors reduce cGMP levels (Ingi et al, 1996b). Cytochrome c oxidase, the terminal enzyme in the mitochondrial electron transport chain, is another potential target for the actions of CO in the cell (Piantadosi, 1996).…”
Section: Introductionmentioning
confidence: 99%